Kombucha’s functional features and fermentation dynamics: a bibliometric assessment in sustainable food production - Alkan, Gözde; Konar Erol, Naime Meric; Yıkmış, Seydi; Er, Hatice; Öğüt, Selim; Yinanç, Abdullah (Frontiers in Sustainable Food Systems, 2025)
Kombucha is a mildly acidic and carbonated functional beverage produced by fermenting tea leaves (Camellia sinensis) with sugar and symbiotic bacteria (SCOBY). It draws attention to traditional fermented beverages due to its antimicrobial and antioxidant properties and positive effects on health. Kombucha’s positive effects on health are based on polyphenols, organic acids, probiotics, and biologically active ingredients. This study evaluates the global spread, academic effect, and publication tendencies of scientific research on Kombucha with a bibliometric approach. Web of Science Core Collection (WoS) catalogue (www.webofknowledge.com) was used to obtain the data. The keyword “Kombucha” was analysed without filtering. In the last 30 years, 1,099 scientific articles have been published in this area and the annual growth rate has been calculated as 9.06%. While China, Brazil, the United States and India were the countries with the highest publication, the countries with the highest citations were India, China and Brazil. When looking at the average number of citations per publication, countries such as Slovenia, Denmark, and the Netherlands were recognized as having the highest academic impact in terms of the quality of studies on Kombucha. Kombucha research is increasingly adopting an interdisciplinary approach, including food science, biochemistry, microbiology, and health sciences. SCOBY optimization, standardization of production processes, and long-term health effects are the areas where more research is needed in the existing literature. Despite the growing literature, there is no comprehensive bibliometric study mapping the development of Kombucha research and future perspectives. The bibliometric analysis we have conducted is the first of its kind. This study contributes to the potential of sustainable food production by revealing the current situation of Kombucha research and future research orientations.